PENGARUH DOSIS KOMBINASI BIOCHAR TANKOS DAN BIOCHAR KOTORAN AYAM TERHADAP EFISIENSI PUPUK NPK MAJEMUK PADA TANAMAN TERUNG PUTIH DI TANAH ALLUVIAL - Alhaddad, Abdul Mujib; Vitri Indrawati, Urai Suci Yulies (Agros Journal of Agriculture Science, 2023)
Production of white eggplant plants continues to increase from year to year, but this year (2023) production has decreased, this is because quite a few farmers have experienced crop failure. The occurrence of crop failure was caused by several obstacles, especially the decreasing fertility level of alluvial soil. To increase the production of white eggplant, farmers are trying to overcome this obstacle by fertilizing. For this reason, in cultivating white eggplant plants, alluvial land needs ameliorant which is easy to obtain and cheap, in addition to providing N, P and K fertilizer, namely by providing tankos biochar. and chicken droppings. This research will conduct an experiment on the effect of providing organic fertilizer Biochar tankos + Chicken Manure biochar on the growth and yield of white eggplant plants in Alluvial soil. The design used in this research was a Completely Randomized Design (CRD) with a treatment dose of organic fertilizer. Biochar tankos + Chicken Manure. Each treatment was repeated 3 times so that 27 experimental units were obtained. The experimental parameters taken were uptake of N, P, K from leaves and weight of white eggplant in harvest 1 and harvest 2. The conclusion drawn was that Biochar Tankos + chicken manure enriched with 75% NPK can help increase the uptake of N, P and K in plants, which increases the supply. The dose of organic fertilizer means that the availability of N, P and K in the soil will also increase. Apart from that, Biochar Tankos + chicken manure enriched with 75% NPK can help increase white eggplant production, where as the dose of organic fertilizer increases, white eggplant production will also increase. Optimum results in the second harvest were obtained in treatment B2 = Chicken Manure Biochar 40 t.ha-1 + NPK 75%, in accordance with the white eggplant yield per ha of the variety. Yasinta. B3M1 treatment with a dose of 1360 g/polyb and compound NPK fertilizer 75% of the recommended 500 g, gave white eggplant production in the first harvest of 194% and the second harvest of 27.45%. Key words: Alluvial, tankos biochar, white eggplant, chicken manure, NPK uptake INTISARIProduksi tanaman terung putih  dari tahun ke tahun terus meningkat namun pada tahun ini (2023) produksinya menurun, hal ini dikarenakan tidak sedikit petani yang mengalami gagal panen. Terjadinya gagal panen diakibatkan karena adanya beberapa kendala, terutama tingkat kesuburan tanah Alluvial  yang menurun. Untuk meningkatkan hasil produksi terung putihnya, para petani berusaha mengatasi kendala tersebut dengan melakukan pemupukan, untuk itu dalam budidaya tanaman terung putih,  lahan Aluvial perlu amelioran yang mudah didapat dan murah harganya, selain pemberian pupuk N,P dan K, yaitu dengan pemberian biochar tankos dan kotoran ayam. Penelitian ini akan melakukan percobaan tentang pengaruh pemberian pupuk organik Biochar tankos + biochar Kotoran Ayam terhadap pertumbuhan dan hasil tanaman terung putih  di tanah Alluvial.  Rancangan yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap (RAL) dengan perlakuan dosis .pupuk organik.  Biochar tankos + Kotoran Ayam. Masing-masing perlakuan diulang sebanyak 3 kali sehingga akan diperoleh 27 unit percobaan. Parameter percobaan yang diambil adalah SerapanN,P,K daun dan Berat terung putih  pada panen 1 dan panen 2. Kesimpulan yang diambil adalah Biochar Tankos + kotoran ayam diperkaya NPK 75%  dapat membantu meningkatkan Serapan N, P dan K tanaman, dimana semakin meningkat pemberian dosis pupuk organiknya maka ketersediaan N,P dan K tanah juga semakin meningkat, selain itu Biochar Tankos + kotoran ayam diperkaya NPK 75%  dapat membantu meningkatkan produksi terung putih, dimana semakin meningkat pemberian dosis pupuk organiknya maka produksi terung putih  juga semakin meningkat. Hasil optimum pada panen kedua didapat pada perlakuan B2 =  Biochar Kotoran Ayam  40  t.ha-1   + NPK 75 %, sesuai dengan hasil terung putih per ha pada varietas. Yasinta. Perlakuan B3M1 dengan dosis 1360 g/polyb dan pupuk NPK Majemuk 75% dari anjuran yaitu 500 g, memberikan produksi terung putih pada panen I sebesar 194% dan panen II sebesar  27.45 %. Kata kunci : Alluvial,  biochar tankos, terung putih, kotoran ayam, Serapan NPK